MANAJEMEN PENINGKATAN MUTU SEKOLAH - Maswan Maswan (Universitas Islam Nahdlatul Ulama Jepara, 2015)
The idea of the emergence of Educational Quality Improvement Management is a management strategy to build a school with its own strength. The potential, that exists in the school system, is empowered maximally in order to produce quality graduates. In the concept of management education, principals or leaders should be able to move all parts of the school in applying all the potential, synergistic, and continuously in the institution maximally. In the managerial concept, principals as top leader of organization should build systems in order to raise the quality of his school by: (a) controlling processes that take place in both curricular and school administration; (B) involving the process of diagnosis and following-up process for diagnosis; and (c) requiring the participation of all parties: teachers, administrative staff, students, parents and experts. The method used is analytical approach to analyze a variety of data conceptually. It used data elaboration through empirical data with the factual analysis in a real setting, especially in educational institutions (schools) to improve the quality of education depends on the leaders (principals). As a leader, the principal must (a) direct, (b) rely on the cooperation more in accomplishing the duty, (c) always instill self-confidence of teachers and administrative staff, (d) always demonstrate how to do something, (e) always develop enthusiastic atmosphere, and (f) always fix errors if any